2017
DOI: 10.3389/fpsyg.2017.00842
|View full text |Cite
|
Sign up to set email alerts
|

Not All Selfies Took Alike: Distinct Selfie Motivations Are Related to Different Personality Characteristics

Abstract: Selfies have become a frequent and commonplace occurrence, though the reasons which lead people to take selfies remain unclear. This research explores what motivates selfie taking, and suggests that this is not a uniform phenomenon and varying motivations may be found among selfie takers. In addition, the connection between these distinct selfie motivations and personality characteristics, including the big five, narcissism, and self-esteem, as well as types of selfie behaviors are examined. At the first stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 39 publications
(63 reference statements)
2
39
0
1
Order By: Relevance
“…For instance, the frequency of selfie postings has been related to exhibitionism and extraversion (Sorokowska et al, 2016), to emotionality and extraversion (Baiocco et al, 2017), and to histrionic personality scores (Sorokowska et al, 2016). Narcissism has been related to posting frequency (Sorokowski et al, 2015;Weiser, 2015;Lee and Sung, 2016) but has been found to be unrelated to motivations for taking selfies (Etgar and Amichai-Hamburger, 2017) and to attitudes toward selfie-taking (Dutta et al, 2018). These studies are relevant to our inquiry to the extent that they assume that selfie-related behaviors may provide information about selfie-takers.…”
Section: Non-verbal Communication In Selfies: Selective Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the frequency of selfie postings has been related to exhibitionism and extraversion (Sorokowska et al, 2016), to emotionality and extraversion (Baiocco et al, 2017), and to histrionic personality scores (Sorokowska et al, 2016). Narcissism has been related to posting frequency (Sorokowski et al, 2015;Weiser, 2015;Lee and Sung, 2016) but has been found to be unrelated to motivations for taking selfies (Etgar and Amichai-Hamburger, 2017) and to attitudes toward selfie-taking (Dutta et al, 2018). These studies are relevant to our inquiry to the extent that they assume that selfie-related behaviors may provide information about selfie-takers.…”
Section: Non-verbal Communication In Selfies: Selective Reviewmentioning
confidence: 99%
“…The same search on the specialist database PubMed yields only about 60 hits, but the bulk of these papers consists of policy commentaries, historical narratives, clinical studies, and health communication applications with limited empirical content. The relatively few papers of interest for the current project may be grouped into three broad categories: studies attempting to connect selfierelated behaviors to personality and motivation (Qiu et al, 2015;Sorokowski et al, 2015;Dhir et al, 2016Dhir et al, , 2017Sorokowska et al, 2016;Sung et al, 2016;Baiocco et al, 2017;Diefenbach and Christoforakos, 2017;Etgar and Amichai-Hamburger, 2017;Karwowski and Brzeski, 2017;Krämer et al, 2017;Musil et al, 2017); studies assessing visual compositional choices for selfies, sometimes in relation to neuropsychological hypotheses (Bruno and Bertamini, 2013;Bruno et al, 2014Bruno et al, , 2015Bruno et al, , 2017Lindell, 2017a,b;Manovich et al, 2017;Schneider and Carbon, 2017;Sedgewick et al, 2017;Babic et al, 2018), and theory papers (Frosh, 2015;Senft and Baym, 2015;Eagar and Dann, 2016;Lim, 2016;Carbon, 2017;Kozinets et al, 2017;Bruno et al, 2018). While interesting, these findings and analyses remain scattered and in need of a common theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“… Etgar and Amichai-Hamburger (2017) have identified three principal motivations behind selfie-taking: selfie-approval, belonging, and documentation. They also suggest that each motivation can be connected to various personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Most research has focused on young people's uses of social media. These studies analyzed youth's social media uses from feminist and queer theory perspectives (Attwood, 2011;De Ridder & Van Bauwel, 2013;Gill, 2007;Ringrose, 2011), but also from psychological (Cedillo & Ocampo, 2016;Etgar & Amichai-Hamburger, 2017) and youth studies perspectives (Bauermeister, 2013;Levine, 2013). Although these studies have been contributing greatly to our understanding of young people's social media uses and sexuality, there is need for understanding the broader cultural discourses in print media's representations of youth, sexuality and social media.…”
Section: )mentioning
confidence: 99%